2019
DOI: 10.17265/2328-2150/2019.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Lung Hydatid Cyst in Children

Abstract: Hydatid infestation of the lung can be primary or secondary. Cystic echinococcosis (CE) is regarded as endemic in Sub-Saharan Africa, however, for most countries only scarce data, if any, exist. This is a retrospective analysis of children below 13 years with lung hydatid cyst admitted in the paediatric surgical ward at NMAH (Nelson Mandela Academic Hospital) in Eastern Cape, South Africa. The study period was from September 2015 to September 2017. The variables studied were age, sex, imagen findings, cysts si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…This is due to the high elasticity and compressibility of the lungs in children. [24][25][26] In one retrospective review of pediatric hydatid cysts from our institution, the lung was found to be the most common site of involvement in 76.5% of the children. 27 Pulmonary hydatid cyst was also the most common indication for thoracotomy in a study from Turkey in which it accounted for 35% of the procedures.…”
Section: Discussionmentioning
confidence: 99%
“…This is due to the high elasticity and compressibility of the lungs in children. [24][25][26] In one retrospective review of pediatric hydatid cysts from our institution, the lung was found to be the most common site of involvement in 76.5% of the children. 27 Pulmonary hydatid cyst was also the most common indication for thoracotomy in a study from Turkey in which it accounted for 35% of the procedures.…”
Section: Discussionmentioning
confidence: 99%